35th AIAA Applied Aerodynamics Conference 2017
DOI: 10.2514/6.2017-3571
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimum Swirl Recovery Vanes for Propeller Propulsion Systems

Abstract: Swirl Recovery Vanes (SRVs) are a row of stationary vanes located downstream of a single-rotating propeller to recover swirl losses and thereby enhance propulsive efficiency. This paper presents the development, application, and experimental validation of a low-order SRVs design tool. The design procedure consists of three steps: first the inflow velocities can be obtained either from the simulation of isolated propeller or from experimental measurements, after which the loading distribution is defined using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A symmetrical airfoil was selected for the entire vane; manufacturing constraints on the minimum thickness led to the selection of a NACA 0009 profile. Later studies [8,9], performed after the work discussed in the current paper had been completed, showed that cambered airfoils typically provide better performance.…”
Section: Modelsmentioning
confidence: 95%
See 1 more Smart Citation
“…A symmetrical airfoil was selected for the entire vane; manufacturing constraints on the minimum thickness led to the selection of a NACA 0009 profile. Later studies [8,9], performed after the work discussed in the current paper had been completed, showed that cambered airfoils typically provide better performance.…”
Section: Modelsmentioning
confidence: 95%
“…However, in the same study, it was found that the total system efficiency was reduced, stressing the importance of proper SRV design and integration. This was addressed by a follow-up work of the same research group [8], focusing on the development, application, and experimental validation of a low-fidelity tool for SRV design. In this work, a measured 2.6% increase in thrust was reported at the design condition for high propeller thrust at low flight velocity and low Reynolds number.…”
Section: σSplmentioning
confidence: 99%
“…In order to improve the convergence of the simulations, the corners of the square duct were slightly rounded, so that the minimum corner radius (at the airfoils' thickest point) would be 1% of the propeller radius, R p . The minimum gap between the propeller tips and duct surface (or tip clearance) was maintained at 0.3% of the propeller radius, leading to a duct chord of approximately 0.217 m. The propeller geometry was based on an existing design, denoted "XPROP", that has been characterized previously in both experimental and numerical studies [15][16][17][18]. The six-bladed wind-tunnel model has a radius of R p = 0.2032 m. Details regarding the propeller geometry, such as chord and twist distributions, can be found in Ref.…”
Section: A Geometrymentioning
confidence: 99%
“…The six-bladed wind-tunnel model has a radius of R p = 0.2032 m. Details regarding the propeller geometry, such as chord and twist distributions, can be found in Ref. [15]. In this study, the blade pitch for the radial location r/R p = 0.7, β 0.7 , was kept at 30°.…”
Section: A Geometrymentioning
confidence: 99%
See 1 more Smart Citation